EVALUASI HARA FOSFOR PADA LAHAN JAGUNG BERDASARKAN KETINGGIAN TEMPAT BERBEDA DI KECAMATAN BALANTAK SELATAN - M. Sipoy, Nena; Ladonu, Moh. Ilham; Mambuhu, Nurmasyita; Katili, Hidayat Arismunandar (Fakultas Pertanian Universitas Tompotika Luwuk, 2025)
Corn (Zea mays) is a very important food crop for society. Currently the government is trying to increase corn production, namely by using fertilizer so that placement is more effective, it is necessary to know the nutrient status around the plant. Phosphorus is one of the three nutrients that plays an important role in plant growth. The land in South Balantak District is mostly land with different heights. Altitude affects phosphorus uptake in the soil. Seeing its easily fixed nature and the presence of phosphorus in the soil which is small but needed in large quantities, the role of P is very important in maintaining the availability of phosphorus for the growth of corn plants. This encourages the need to evaluate the current and available P nutrient status, especially in corn fields in South Balantak District. The aim of this research is to determine the phosphorus nutrient content in corn fields at different altitudes according to land units in South Balantak District. This research was carried out in October 2023 – January 2024. Four representative samples were taken of soil from corn fields at different heights in South Balantak District. This research uses a descriptive survey method. The results of soil analysis of phosphorus nutrients at the research location at an altitude of 0 to 150 meters above sea level were classified as low. Meanwhile, at an altitude of > 150 to 250 meters above sea level, the phosphorus content is classified as moderate.